Social responsibility in a company distribution of electricity - Camillo, Rodrigo; Ely, Bruno José; Souto Bolzan Medeiros, Flaviani; Antonini Bortoluzzi, Daiane; da Silva Waechter, Lucélia; Obregon, Sandra Leonara (Revista de Administração da UFSM, 2015)
In the context of social, economic and technological changes through which pass the countries and organizations, these transformations arising from wars, inequality, technological advances and shortage of raw materials, there has been a major concern in establishing ethical principles that lead to realization of shares social responsibility in organizations. In this sense, the present article aims to propose actions to improve the Social Responsibility Programme, based on the Ethos Institute in an electricity distributor. For this, the methodological procedures, the study is characterized as qualitative, descriptive type, being developed through semi-structured interviews with seven employees of the company. Among the results was possible to verify that employees are aware of the role that energy company has been developing for the continuous pursuit of quality, informally demonstrating a certain degree of satisfaction with the company. At the same time, research shows some ignorance on the part of employees about the work that is now developed by the company, thus directing to stagnation of information.